Epidemiological analysis of hospitalizations for acute myocardial infarction in Teresina-PI between 2017 and 2022 (Research, Society and Development, 2023)
Introduction: Acute myocardial infarction is an important cardiac condition, which, when not treated quickly and properly, results in potential myocardial dysfunction. In Brazil, cardiovascular diseases are at the top of the causes of death, among which coronary artery disease was the main one from 1990 to 2019. Cardiac infarction accounted for 54% of hospital admissions across the country between 2008 and 2019, highlighting its prevalence in the country. Objective: To analyze hospitalizations due to acute myocardial infarction in Teresina-PI between 2017 and 2023. Methodology: Observational, descriptive epidemiological study based on data collected in the SUS Hospital Information System. Results: There were 8,457 hospitalizations for the condition studied in Teresina, which cost R$ 23,854,458.54 to the public coffers. The highest number of hospitalizations was verified in 2019. The age group with the highest number of hospitalizations was 60 to 69 years old, and almost half of the patients with a record about color/race were classified as brown. Conclusion: There were a large number of hospitalizations due to infarction in Teresina, most of them by men, on an emergency basis, but the highest mortality rate was observed in females.